Biomarcadores lipídicos associados à doença arterial coronariana (DAC): contribuições da lipidômica - OLIVEIRA, Lívia Mariane Castelo Branco Reis Coutinho de (2019)
Background: The relationship between elevated blood lipid levels and coronary artery disease has already been established; however, the lipidic approach allows the evaluation of other lipid species that have not been evaluated using conventional strategies. Here, we attempted to identify the lipid biomarkers associated with Coronary Artery Disease, through the use of lipidomics. Methods and Results: A cross-sectional study was performed with 292 consecutive patients who underwent coronary angiography. For the lipid analysis, lipid extraction was performed using the Bligh and Dyer protocol. The mass spectrometry data with laser desorption / matrix-assisted ionization were evaluated with univariate and multivariate analysis. Lipids identified as potential biomarkers of atherogenesis were identified using the online Lipid Maps database, followed by analysis of metabolic pathways using Cytoscape software. Patients were divided into two groups: significant coronary artery disease (n = 188) and no significant coronary artery disease (n = 104). There were differences between the two groups regarding age, sex, high density lipoprotein cholesterol, high density lipoprotein cholesterol / triglyceride ratio, high density lipoprotein cholesterol / low density lipoprotein cholesterol ratio, triglycerides and apolipoprotein A. When lipidic and mass spectrometry were applied, nine lipid species were identified and quantified, with seven lipid species glycerophosphoethanolamine PE (O-46: 5; P-46: 4; P-49: 3); Glycerophosphocholine PC (O-46: 4, P-46: 3); Glycerophospitoinositol PI (O-43: 0); Glicerofosfoserina PA (O-43: 3) presented increased concentrations in the group of patients with significant Coronary Artery Disease.In the group without coronary artery disease increased lipid species were observed: glycerophosphoryin PS (20: 0) and lysophosphate LPA (P-20: 0). Conclusions: The lipidic analysis by lipidomic identified, in the studied group, the presence of increased metabolites, determining a possible association between Coronary Artery Disease and elevation of these lipid species. Such metabolites may help in the knowledge of the genesis of atherosclerosis, which may in the future be useful in the investigation of cardiovascular diseases, especially Coronary Artery Disease. Further studies are needed to confirm this data.